Analysis of Budgetary Slack Trigger Determinants in State Universities (Universitas Negeri Semarang, 2022)
This study aims to analyze the factors that are thought to influence the occurrence of budgetary slack. The method used in this study is a quantitative approach, with a research sample of 50 active employees at the State University of Semarang. The data processing method used in this study is multiple linear regression using SPSS 26 software. Based on the analysis that has been carried out, several research results obtained that budget participation, organizational commitment and self-esteem have a significant negative effect on the occurrence of Budgetary Slack. This means that when a company is able to increase the budget participation of its employees and is supported by the high organizational commitment of its employees, it will significantly minimize the occurrence of fraudulent financial reporting such as Budgetary Slack. Furthermore, information asymmetry and self-esteem variables have a significant positive effect on the occurrence of Budgetary Slack.